Investigação de citotoxicidade, mecanismo de morte e toxicidade de análogos de chalconas: LQFM064, LQFM157 e LQFM178 - Cabral, Bruna Lannuce Silva (2016)
In the search for new antineoplastic agents, chalcones, intermediate compounds in flavonoid biosynthesis, are an interesting group of compounds, since they present considerable cytotoxic activity against a range of neoplasms and relatively easy chemical structural modifications. Therefore, the aim of this study was to analyse the cytotoxic potential of chalcone-type compounds, and evaluate the mechanisms of cell death triggered by the most promising prototype on the human mammary adenocarcinoma cell line MCF-7. To do so, a cytotoxicity assessment of three chalcone-type (LQFM064, LQFM157 and LQFM178) was carried out using a tetrazolium salt reduction (MTT) method. Taking into account that LQFM064 was considered the most promising of the compounds analysed in terms of cytotoxicity, further tests to elucidate the cell death pathways and to evaluate the safety profile were carried out. Morphological analysis of the cells was performed by light microscopy and fluorescence. Cellular apoptosis induction mechanisms were investigated by analyzing death markers using the flow cytometry technique. Safety aspects of the compound were also investigated. Cytotoxicity was analysed using the OECD test method of incorporating the neutral red dye into murine fibroblast cells (3T3), and using the result of this assay to predict LD50. Myelotoxic potential was assessed by using the clonogenic assay of granulocyte macrophage colony-forming units (CFUGM). The data were analyzed by Analysis of Variance (ANOVA) and a posteriori by the Tukey test or t-test. The means were considered statistically significant when P < 0.05. The LQFM 064 prototype was cytotoxic for the MCF-7 (IC50 = 21 µM) and 3T3 (IC50 = 30 µM) lineages in a concentrationdependent manner. Treatment of tumor cells with LQFM064 induced morphological changes suggestive of apoptosis. In addition, several biochemical alterations indicated cell death by apoptosis, such as: cell cycle arrest in the G0/G1 phase, the outgrowth of phosphatidylserine, increased expression of caspases -3/7, -8 and -9, reduced mitochondrial membrane potential and increased generation of Reactive Oxygen Species (ROS). Activation of both apoptotic pathways was also seen through modulation of the proteins involved in the extrinsic and intrinsic pathways. The compound was myelotoxic to normal bone marrow cells in a concentration-dependent manner. However, this toxicity was lower for normal than for tumor cells. It was therefore concluded that the LQFM064 compound triggered alterations suggestive of apoptosis in MCF-7 tumor cells, and could be considered promising as an antitumor drug prototype.